Urban rail vehicle wheel with narrow hardness range and production method thereof

By adopting continuous tread spray quenching and overall high-temperature tempering treatment in wheel production, the problem that existing wheels cannot meet the narrow hardness range and low tread near-surface hardness requirements are solved, and the wheel hardness distribution is optimized and improved The performance and life of the wheels.

CN115558745BActive Publication Date: 2025-02-14МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211184813.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-02-14
Estimated Expiration
2042-09-27

AI Technical Summary

Technical Problem

During the tempering stage, existing wheels cannot meet the performance requirements of narrow hardness range and low tread near surface hardness, resulting in problems such as non-rounding during use, affecting the smoothness and safety of the vehicle.

Method used

The tread continuous spray and quenching method is used to cool, combined with the overall high-temperature tempering treatment, the hardness distribution of the wheel is controlled, the hardness of the tread near the surface layer without reducing the hardness of the tread sub-surface layer and the inner rim, achieving wheel production in a narrow hardness range.

Benefits of technology

The hardness of the wheel tread near the surface is reduced, the chance of non-rounding is reduced, the wear stability and service life of the wheel are improved, and the line operation and maintenance costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115558745B_ABST
    Figure CN115558745B_ABST
Patent Text Reader

Abstract

The present invention provides a narrow hardness range urban rail vehicle wheel and a production method thereof, wherein the tempering average temperature T 回 510~565℃; T 回 =595‑exp[5.81×C+1.14×(Cr+Mo+Ni)+2.11×V]; The present invention adopts appropriately high temperature tempering, and the C in the cementite is "heat activated". As time goes by, the diffusion of C causes the cementite to "twist → deform → break → aggregate → grow", and the lamellar pearlite will undergo cracking and spheroidization evolution. At the same time, the adjacent ferrite is squeezed together under the action of thermal expansion, which also accelerates the cracking and spheroidization of the cementite until the ferrite boundaries contact each other, and finally forms granular pearlite, resulting in a decrease in hardness. The scheme of the present invention makes the pearlite near the surface of the wheel tread preferentially crack and spheroidize to reduce the hardness, but the pearlite morphology of the subsurface of the tread and the inside of the rim is basically unchanged, and the hardness does not change much.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of railway wheel preparation, and in particular relates to an urban rail vehicle wheel with a narrow hardness range and a production method thereof. Background Art

[0002] Wheels are key running components of rail vehicles. During service, they may suffer from non-rounding and other types of surface damage under the repeated effects of wheel-rail contact stress and vibration impact, which directly affects the smoothness of vehicle operation, reduces riding comfort, and in severe cases reduces vehicle operation safety. Studies have shown that the surface damage of wheel treads is closely related to wheel steel material factors such as the hardness level, hardening rate, and hardened layer depth in the wheel-rail contact area. However, this correlation is not a simple increasing or decreasing relationship. Through user-side practical big data feedback, on certain subway lines in some cities in China, the lower hardness of the wheel tread near the surface may be beneficial to improve problems such as early non-rounding of the wheel. Therefore, a well-known domestic rail vehicle company recently proposed special supply requirements for wheels with a narrow hardness range and low tread near the surface hardness.

[0003] In the prior art, the average temperature of the wheel during the tempering stage is usually lower than 500°C, the purpose of which is to decompose the martensitic structure formed near the surface of the wheel tread during the quenching stage, which is harmful to the performance, thereby improving the subsequent finishing cutting performance, while retaining the morphology of the lamellar pearlite in the subsurface of the rim and the matrix without affecting the strength level of the wheel. However, the wheels produced still cannot meet the performance requirements of wheels with a narrow hardness range and low hardness near the surface of the tread. Summary of the invention

[0004] The purpose of the present invention is to provide an urban rail vehicle wheel with a narrow hardness range and a production method thereof. In response to the differentiated needs of wheel users for the hardness distribution of wheel rims, a production method for urban rail vehicle wheels with a narrow hardness range and the produced wheels are provided, which can reduce the hardness of the near-surface layer of the wheel tread without almost reducing the sub-surface layer of the wheel tread and the internal hardness of the rim, thereby obtaining a rim cross-section hardness distribution that meets design expectations.

[0005] The specific technical solutions of the present invention are as follows:

[0006] The present invention provides a method for producing a wheel for an urban rail vehicle with a narrow hardness range, comprising the following steps:

[0007] S1: Take the rolled blank wheel into the furnace for heating and heat preservation;

[0008] S2: taking out the wheel obtained in step S1 and transferring it to a horizontal quenching table, cooling it by continuous tread quenching, during which the wheel rotates;

[0009] S3: The wheel obtained in step S2 is transported to a tempering furnace for tempering treatment.

[0010] In step S1, the wheel is heated to Ac3+(60-90)°C and kept warm for 1-1.5h to ensure that the entire wheel is evenly heated and fully austenitized.

[0011] In step S2, continuous tread quenching is performed using 6 box-type spray guns evenly distributed along the circumference of the wheel, and the water flow rate of each spray gun is equal, that is, the flow rate L of each spray gun is 18-20m 3 / h, water outlet speed 6~8m / s;

[0012] The idea of ​​controlling the flow rate of the present invention is: within a certain range, the hardness of the wheel increases with the increase of the flow rate. When the flow rate reaches a certain level (long-term practice believes that the critical total water flow rate is 100-110 tons per hour, that is, the flow rate of each spray gun is 16.7-18.3 tons), the increase in wheel hardness becomes very small. Taking into account both the effect and water consumption, the present invention sets the flow rate L of each spray gun to 18-20m 3 / h. The purpose of setting the water outlet speed is to break the water vapor film. If the speed is too low, it will affect the cooling and heat exchange effect; if the speed is too high, it will splash significantly and affect the working environment.

[0013] In step S2, the water discharge direction of the spray gun is along the rotation direction of the wheel, and the water column and the tread tangent are at an angle of 30 to 35 degrees. Such an angle allows the water flow to better adhere to the wheel tread surface, ensuring a better cooling and heat exchange effect.

[0014] In step S2, the quenching time t is 240 to 320 seconds. The specific quenching time depends on the wheel rim thickness B. Specifically:

[0015] For wheels with rim thickness B≤75mm, the quenching time is controlled to be 240s≤t≤270s;

[0016] For wheels with a rim thickness of 75<B≤85mm, the quenching time is controlled at 270s<t≤320s.

[0017] After quenching, the wheel tread surface temperature is lower than 100℃, ensuring that the entire rim area is worn to the limited area and the pearlite structure transformation is completed.

[0018] In step S2, the wheel rotates at an angular velocity of 55 to 65° / s.

[0019] In step S2, the obtained wheel has a large rim cross-section, and the cooling rate is distributed in a gradient along the radial direction (i.e., the rim depth direction), which inevitably leads to a gradient change in the spacing of pearlite sheets from the near surface of the tread to the inside of the rim. The spacing of pearlite sheets near the surface of the tread is relatively fine, and the spacing of pearlite sheets inside the rim is relatively coarse. The larger the cross-sectional size of the workpiece, the greater the difference in cooling rate between the inside and outside, and the more obvious the cooling rate gradient, so that the microstructure presents the basic characteristic of "fine on the surface and coarse on the inside". This is the organizational element premise that the present invention adopts overall high-temperature tempering treatment to reduce the hardness of the near surface of the wheel tread while almost not reducing the hardness of the sub-surface of the tread and the inside of the rim.

[0020] Furthermore, the average pearlite plate spacing from the near surface of the wheel rim tread to the inside of the rim obtained in step S2 is 100 to 170 nm.

[0021] In step S3, the obtained wheel is taken out and transferred to the tempering furnace through the cooling bed. The transfer time of the cooling bed is 5 to 8 minutes. During this process, the heat inside the rim is transferred to the surface layer near the tread, resulting in temperature recovery, so that the temperature of the surface layer near the tread of the wheel increases, and finally the temperature of the entire rim is uniform, and the temperature is stabilized at 420 to 470°C, so that the wheel can be brought into the tempering furnace with heat, saving the heating energy consumption in the tempering stage.

[0022] In step S3, the tempering temperature is T 回 The tempering temperature is 510~565℃ and kept warm for 2.5~3h. The choice of tempering temperature depends on the total content of C, Cr, Mo, Ni and V elements in the steel. If the content of C+Cr+Mo+Ni+V is low, a higher tempering temperature is selected within this range; if the content of C+Cr+Mo+Ni+V is high, a lower tempering temperature is selected within this range. Specific tempering average temperature T 回 The setting follows the following formula:

[0023] T 回 =595-exp[5.81×C+1.14×(Cr+Mo+Ni)+2.11×V];

[0024] In the formula, the index value of each element = the content of the element in the steel × 100.

[0025] T 回 The unit is ℃;

[0026] It is worth noting that, under normal circumstances, in order to retain the morphology of lamellar pearlite without affecting the strength level of the wheel, the temperature of the wheel tempering stage is lower than 500°C. Firstly, the martensitic structure formed near the surface of the wheel tread in step S2 of the present invention, which is harmful to the performance, is decomposed, thereby improving the cutting performance; secondly, the residual stress state and matching between the wheel rim and the spoke plate are improved.

[0027] In the design of this application, the tempering temperature used is high, and the wheel C, Cr, Mo, Ni, and V elements can improve the stability of supercooled austenite, resulting in a pearlite structure with finer interlamellar spacing. According to the principle of the present invention, the finer the interlamellar spacing, the more sensitive the pearlite is to the tempering temperature, and the easier it is for its morphology to change during high-temperature tempering, resulting in varying degrees of hardness attenuation. Therefore, the total content of C, Cr, Mo, Ni, and V is negatively correlated with the tempering temperature. The tempering temperature that meets the formula designed by the present invention enables the wheel to obtain the desired structure and performance.

[0028] After the tempering treatment in step S3, the wheel is taken out and air-cooled, and a finished wheel is obtained through subsequent machining and other processes. Specifically, a circular blade with a diameter of φ20 to φ25 mm is used to perform cutting machining on the rim surface, wherein the total radial machining amount of the single-side tread is 6 to 9 mm, the machining line speed is 170±20 m / min, the cutting depth is 0.4 to 0.6 mm per cut, the feed rate is 0.8 to 1.0 mm per revolution, and the roughness Ra of the finished tread is 3.2 to Ra 6.3.

[0029] The present invention provides a wheel for urban rail vehicles with a narrow hardness range, comprising a wheel having the following mass percentage components:

[0030] C 0.54~0.63%, Cr 0.12~0.35%, Mo 0.04~0.10%, Ni 0.05~0.10%, V 0.02~0.06%.

[0031] Preferably, the urban rail vehicle wheels with a narrow hardness range include wheels with the following mass percentage components:

[0032] C 0.54~0.63%, Si 0.20~0.50%, Mn 0.70~0.90%, Cr 0.12~0.35%, Mo0.04~0.10%, Ni 0.05~0.10%, V 0.02~0.06%, P≤0.020%, S≤0.015%, and the rest are Fe and unavoidable impurities.

[0033] The urban rail vehicle wheel with a narrow hardness range provided by the present invention has a microstructure of pearlite + a small amount of ferrite at room temperature, and the average ferrite volume fraction at the wear limit, that is, 35mm from the finished tread, is 3% to 6%, the average pearlite sheet spacing is 140 to 170nm, and the grain size is greater than 7.5. Compared with the wheel obtained by the traditional process, the pearlite structure near the surface of the wheel tread obtained by the scheme of the present invention undergoes different degrees of deformation, fracture, and even partial spheroidization, and the obtained hardness is lower. Compared with the traditional process, the hardness of the tread near the surface is reduced by 4% to 6%, while the pearlite structure morphology and hardness of the sub-surface of the tread and the inside of the rim are almost unchanged. Compared with the traditional process, the cross-sectional hardness range is reduced by 35% to 55%, and the cross-sectional hardness range is less than 20HB, reaching the design expectation of the narrow hardness range.

[0034] Some descriptions are explained in the present invention:

[0035] 1) The wheel tread near surface layer mentioned in the present invention refers to the area within 10 mm from the tread, the wheel tread sub-surface layer refers to the area 10-15 mm from the tread, and the inside of the rim refers to the area near the wear limit, i.e., 35 mm from the tread.

[0036] 2) The cross-sectional hardness range described in the present invention refers to the absolute difference between the maximum hardness and the minimum hardness on the cross-sectional surface of the wheel rim. For the convenience of calculation, the hardness difference between 5mm from the finished tread and 35mm from the tread is generally taken. The hardness of the near-surface layer is reduced by 4% to 6% by the present invention. The maximum hardness may appear in the near-surface layer or in the sub-surface layer, but the position where the minimum hardness appears remains unchanged, which is still inside the rim. The calculation method of the cross-sectional hardness range is still the maximum hardness minus the minimum hardness. If the maximum hardness appears in the sub-surface layer, the hardness difference between the sub-surface layer (15mm from the finished tread) and the hardness at 35mm from the tread is taken.

[0037] 3) The urban rail vehicle wheel with a narrow hardness range of the present invention refers to the cross-sectional hardness range of the wheel rim. The cross-sectional hardness range of the present invention is less than 20HB, meeting the narrow hardness range requirement.

[0038] The solution of the present invention is aimed at the differentiated needs of wheel users. Based on the essential characteristics of the "gradient distribution" of the radial pearlite plate spacing of the rim after the wheel tread is spray-quenched and cooled, the overall high-temperature tempering treatment is adopted to achieve secondary regulation of the hardness of the rim near the surface of the tread and below the surface of the tread. Figure 3 As shown, after the wheel tread is spray-quenched in Example 1, the pearlite plate spacing in the radial direction from the tread of the rim changes from 130nm to 170nm in a certain regular pattern.

[0039] The design principle of the present invention is that, during the cooling stage of the wheel quenching heat treatment, the cooling rate is distributed in a gradient along the radial direction (i.e., the depth direction of the rim) due to the large cross-section of the rim, which inevitably leads to a gradient change in the spacing of the pearlite sheets from the tread surface to the inside of the rim. The spacing of the pearlite sheets near the tread surface is relatively small, and the spacing of the pearlite sheets inside the rim is relatively large. Figure 1 , Figure 2 As shown, tempering treatment is performed at an appropriately high temperature, and C in cementite is "heat activated". As time goes by, C diffusion causes cementite to "twist → deform → break → aggregate → grow" in sequence. Lamellar pearlite will undergo cracking and spheroidization evolution. At the same time, the adjacent ferrite is squeezed together under the action of thermal expansion, which also accelerates the cracking and spheroidization of cementite until the ferrite boundaries contact each other, and finally forms granular pearlite, resulting in a decrease in hardness. However, the above-mentioned cracking and spheroidization evolution trends of pearlite with different interlamellar spacing are different in sequence, and cracking and spheroidization do not occur synchronously at the same temperature. The finer the pearlite interlamellar spacing, the thinner the cementite is, and cracking and spheroidization evolution occurs preferentially under the action of thermal diffusion driving force. Accordingly, the use of the scheme of the present invention can make the pearlite near the surface of the wheel tread preferentially crack and spheroidize to reduce the hardness, but the pearlite morphology of the subsurface of the tread and the inside of the rim is basically unchanged, and the hardness does not change much.

[0040] Compared with the prior art, the present invention: 1) meets the differentiated needs of wheel users, reduces the hardness of the tread near the surface without changing the hardness of other parts of the rim, and realizes a narrowing of the radial hardness range of the wheel rim; 2) low near-surface hardness is conducive to improving the early service performance of newly installed wheels, and more optimal wheel-rail profile geometric size matching can be obtained more quickly during the running-in stage, reducing the probability of non-circularity; 3) the narrow rim hardness range is conducive to improving the wear stability and uniformity of the wheel throughout its life cycle, reducing the frequency of unplanned turning and repair, extending the service life of the wheel, and reducing the line operation and maintenance costs; 4) the process flow is simple and easy, and can be realized without the need for production line equipment modification, which is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The schematic diagram of the microstructure distribution at different depths of the wheel rim obtained by the traditional tempering process, in which 1 is ferrite and 2 is cementite;

[0042] Figure 2 The figure is a schematic diagram of the microstructure distribution at different depths of the wheel rim obtained by the tempering process of the present invention; based on the essential characteristics of the "gradient distribution" of the radial pearlite sheet spacing of the rim after the wheel tread is spray-quenched and cooled and the difference in sensitivity to the tempering temperature, a properly high temperature tempering treatment is adopted, so that the cementite in the pearlite near the surface of the tread aggregates and grows under the action of thermal diffusion and the thermal expansion and compression of ferrite, and preferentially undergoes cracking and spheroidization evolution, while the morphology of the pearlite in the sub-surface of the tread and inside the rim is almost unchanged;

[0043] Figure 3 The distribution of the pearlite sheet spacing along the radial direction from the tread of the wheel rim at the end of the wheel tread quenching in Example 1 (without tempering);

[0044] Figure 4 The wheel tread of Example 1 is spray quenched and the temperature recovery condition before entering the tempering furnace after spray quenching;

[0045] Figure 5 This is the microstructure of the tread surface (3-7 mm from the tread) of the wheel of Example 1 at the end of quenching and cooling (without tempering), and the pearlite is in the form of fine lamellar layers;

[0046] Figure 6 The microstructure of the finished wheel tread near the surface (3 to 7 mm from the tread) in Example 1 has changed the original lamellar pearlite morphology, and the cementite has undergone obvious cracking and spheroidization;

[0047] Figure 7 The microstructure of the subsurface layer (10-15 mm from the tread) of the finished wheel of Example 1 is shown, and the original lamellar pearlite morphology at the end of quenching and cooling is almost unchanged;

[0048] Figure 8 This is the microstructure of the tread surface (3-7 mm from the tread) of the wheel of comparative example 1 at the end of quenching and cooling (without tempering), and the pearlite is in the form of fine lamellar layers;

[0049] Fig. 9 This is the microstructure of the wheel tread near the surface (3 to 7 mm from the tread) of Comparative Example 1, and the original lamellar pearlite morphology at the end of quenching and cooling is almost unchanged;

[0050] Fig.10 The microstructure of the subsurface layer (10-15 mm from the tread) of the wheel of Comparative Example 1 is shown, and the original lamellar pearlite morphology at the end of quenching and cooling is almost unchanged;

[0051] Fig.11 The radial hardness distribution at the nominal rolling circle of the wheels of Example 1 and Comparative Example 1;

[0052] Fig.12 The radial hardness distribution at the nominal rolling circle of the wheels of Example 2 and Comparative Example 2;

[0053] Fig.13 The radial hardness distribution at the nominal rolling circle of the wheels of Example 3 and Comparative Example 3. DETAILED DESCRIPTION

[0054] The scheme of the present invention is described in detail with reference to the accompanying drawings and embodiments.

[0055] Example 1

[0056] A wheel for urban rail vehicles with a narrow hardness range comprises the following components in mass percentage: as shown in Table 1, P 0.012% and S 0.011% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0057] The method for producing urban rail vehicle wheels with a narrow hardness range in Example 1 comprises the following specific steps:

[0058] S1. Put the rolled blank wheel into the furnace and heat it to 845±10℃, and keep it evenly heated for 1h to ensure that the whole wheel is evenly heated and fully austenitized.

[0059] S2. Take out the fully austenitized wheel and transfer it to the horizontal quenching table. Use the tread continuous spray quenching method to cool it. Six box-type spray guns are evenly distributed along the circumference of the wheel. The water flow rate of each spray gun is equal. The flow rate L of each spray gun is 18m 3 / h, water outlet speed 8m / s. During the quenching process, the wheel rotates at an angular velocity of 65° / s, the water outlet direction is along the wheel rotation direction, and the water column and the tread tangent are at an angle of 35°; the rim thickness B is 85mm, the quenching time t is 320s; the wheel tread surface temperature after quenching is less than 100℃. Due to the large cross-section of the rim, the cooling rate is gradiently distributed along the radial direction (i.e., the rim depth direction). After quenching, if Figure 3 As shown, the spacing of pearlite sheets from the surface of the tread to the inside of the rim of the wheel must show a gradient change, and the average pearlite sheet spacing ranges from 130 to 170nm. The spacing of pearlite sheets near the surface of the tread is relatively small, and the spacing of pearlite sheets inside the rim is relatively large.

[0060] S3, after the quenching, the wheel is transferred from the cooling bed to the tempering furnace for 6 minutes. Figure 4 As shown in the figure, in this process, the heat inside the rim is transferred to the surface layer of the tread, causing the temperature to rise, so that the temperature of the surface layer of the wheel tread can be brought into the tempering furnace with heat, saving heating energy consumption in the tempering stage. Subsequently, the wheel is loaded into the tempering furnace and the average temperature is T 回 The wheel was tempered at 563℃ and kept warm for 2.5h. After tempering, the wheel was taken out and air-cooled. The wheel surface was machined with a φ20mm diameter circular blade. The total machining amount of the single-side tread was 6mm, the machining line speed was 150m / min, the cutting depth was 0.5mm per cut, the feed rate was 1.0mm per revolution, and the finished tread roughness was Ra 6.3.

[0061] During the cooling stage of the wheel quenching heat treatment, the cooling rate is distributed in a gradient along the radial direction (i.e., the depth direction of the rim) due to the large cross-section of the rim. This will inevitably lead to a gradient change in the pearlite sheet spacing from the tread surface to the inside of the rim. The pearlite sheet spacing near the surface of the tread is relatively fine, and the pearlite sheet spacing inside the rim is relatively coarse. When tempering is performed at an appropriately high temperature, the C in the cementite is "thermally activated". As time goes by, the diffusion of C causes the cementite to "distort → deform → fracture → aggregate → grow up" in sequence. The lamellar pearlite will undergo cracking and spheroidization evolution. At the same time, the adjacent ferrite, under the action of thermal expansion, squeezes together and accelerates the cracking and spheroidization of the cementite until the ferrite boundaries contact each other, and finally forms granular pearlite, resulting in a decrease in hardness. However, the above-mentioned cracking and spheroidization evolution trends of pearlite with different sheet spacing are different in order, and cracking and spheroidization do not occur synchronously at the same temperature. The finer the pearlite sheet spacing, the thinner the cementite is, and cracking and spheroidization evolution occurs first under the action of thermal diffusion driving force. Based on this, the adoption of the scheme of this embodiment can cause the pearlite near the surface of the wheel tread to preferentially crack and spheroidize to reduce the hardness, but the morphology of the pearlite in the sub-surface of the tread and inside the rim remains basically unchanged, and the hardness also does not change much, thereby achieving secondary regulation of the hardness near the surface of the tread, the sub-surface of the tread, and the inside of the rim.

[0062] Table 1 Main chemical components and technical parameters of wheels of the embodiment and comparative example (wt%)

[0063]

[0064] Comparative Example 1

[0065] A wheel comprises the following components in mass percentage: as shown in Table 1, P 0.011% and S 0.011% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0066] The preparation steps and relevant technical parameters of the wheel are the same as those of Example 1, but different from Example 1 is that the wheel of Comparative Example 1 is for decomposing the martensitic structure formed near the surface of the wheel tread during the spray quenching stage, which is harmful to the performance of the wheel, to improve the residual stress state and matching between the wheel rim and the spoke plate, while keeping the morphology of the lamellar pearlite below the surface of the tread unaffected. The tempering average temperature of the wheel of Comparative Example 1 is 490°C.

[0067] like Figure 5 As shown in Figure 1, at the end of quenching and cooling of the wheel of Example 1 (without tempering), the pearlite near the surface of the tread (3 to 7 mm from the tread) is in the form of fine lamellar layers. Take the finished wheel of Example 1, take one sample each at 3 to 7 mm and 10 to 15 mm from the tread in the radial direction for microstructural analysis, and the results are as follows: Figure 6 , Figure 7As shown in the figure, the pearlite morphology near the surface of the tread has changed significantly, the cementite is twisted and deformed, and fractured and spheroidized, while the pearlite morphology of the subsurface of the tread has hardly changed and still retains the lamellar shape. The pearlite morphology of the wheel obtained in comparative example 1 along the radial direction has hardly changed during the tempering stage, as shown in the figure. Figure 8-Figure 10 As shown, the microstructure of the near-surface and sub-surface layers of the tread is still in the form of lamellar pearlite, and presents a gradient distribution pattern of "fine on the surface and coarse on the inside".

[0068] The radial hardness distribution of the nominal rolling circle of the wheels of Example 1 and Comparative Example 1 is as follows Fig.11 As shown. The radial hardness gradient of the wheel of comparative example 1 is obvious, and the hardness difference between the tread surface and the inside of the rim is 31HB, while the hardness of the tread surface of the wheel of embodiment 1 is significantly reduced, and the gradient is not obvious. The hardness difference between the tread surface and the inside of the rim is only 19HB, and the hardness of the tread sub-surface and the inside of the rim is equivalent to that of the wheel of comparative example 1, achieving the design expectation. The microstructure of the wheel of embodiment 1 at room temperature is pearlite + a small amount of ferrite. The ferrite content at the wear limit (i.e. 35mm away from the finished tread) is 5.6±0.2%, the pearlite plate spacing is 165±4nm, and the grain size is 8.5.

[0069] According to BS EN 13262 "Railway Applications - Wheelsets and Bogies - Wheels - Product Requirements", a tensile test specimen was taken 15 mm below the tread of the finished wheel, and a tensile test was performed in accordance with GB / T 228.1 "Tensile Test of Metallic Materials Part 1: Test Method at Room Temperature". According to BS EN 13262 "Railway Applications - Wheelsets and Bogies - Wheels - Product Requirements", a Charpy impact specimen was taken at three specified positions on the rim of the finished wheel, and a pendulum impact test was performed at room temperature and -20°C in accordance with GB / T 229 "Charpy Pendulum Impact Test Method for Metallic Materials". The mechanical properties of the wheel rims of Example 1 and Comparative Example 1 are shown in Table 2. It can be seen that the use of the scheme of the present invention has little effect on the conventional mechanical properties of the key parts of the wheel rim, and can ensure the service safety of the wheel.

[0070] Table 2 Main mechanical properties of the wheel rim of the embodiment and the comparative example

[0071]

[0072] Example 2

[0073] A wheel for urban rail vehicles with a narrow hardness range comprises the following components in mass percentage: as shown in Table 1, P 0.010% and S 0.011% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0074] The method for producing urban rail vehicle wheels with a narrow hardness range of Example 2 comprises the following specific steps:

[0075] S1. Put the rolled blank wheel into the furnace and heat it to 855±10℃, and keep it evenly heated for 1h15min to ensure that the whole wheel is evenly heated and fully austenitized.

[0076] S2. Take out the fully austenitized wheel and transfer it to the horizontal quenching table. Use the tread continuous spray quenching method to cool it. Six box-type spray guns are evenly distributed along the circumference of the wheel. The water flow rate of each spray gun is equal. The flow rate L of each spray gun is 19m 3 / h, water outlet speed 7m / s. During the quenching process, the wheel rotates at an angular velocity of 60° / s, the water outlet direction is along the wheel rotation direction, and the water column and the tread tangent are at an angle of 35°. The rim thickness B is 75mm, and the quenching time t is 270s. The wheel tread surface temperature after quenching is less than 100℃.

[0077] S3, after the quenching, the wheel is transferred to the tempering furnace through the cooling bed for 8 minutes, and then the wheel is loaded into the tempering furnace and the uniform temperature is T 回 The wheel was tempered at 545℃ and kept warm for 2h45min. After tempering, the wheel was taken out and air-cooled. The wheel rim surface was machined with a circular blade of φ25mm in diameter. The total machining amount of the single-side tread was 8mm, the machining line speed was 170m / min, the cutting depth was 0.6mm per cut, the feed rate was 0.8mm per revolution, and the finished tread roughness was Ra 6.3.

[0078] Comparative Example 2

[0079] A wheel comprises the following components in mass percentage: as shown in Table 1, P 0.009% and S 0.009% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0080] The preparation steps and relevant technical parameters of the wheel are the same as those of Example 2. However, the difference from Example 2 is that the tempering average temperature of the wheel of Comparative Example 2 does not exceed 500°C, and the tempering is performed at an average temperature of 480°C.

[0081] The radial hardness distribution of the nominal rolling circle of the wheels of Example 2 and Comparative Example 2 is as follows: Fig.12 As shown. The radial hardness gradient of the wheel of comparative example 2 is obvious, and the hardness difference between the tread surface and the inside of the rim is 33HB, while the hardness of the tread surface of the wheel of embodiment 2 is significantly reduced, and the gradient is not obvious. The hardness difference between the tread surface and the inside of the rim is only 17HB, and the hardness of the tread sub-surface and the inside of the rim is equivalent to that of the wheel of comparative example 2, achieving the design expectation. The microstructure of the wheel of embodiment 2 at room temperature is pearlite + a small amount of ferrite. The ferrite content at the wear limit (i.e. 35mm away from the finished tread) is 4.5±0.2%, the pearlite interlamellar spacing is 151±3nm, and the grain size is 8.0.

[0082] The tensile mechanical properties and Charpy impact energy of the wheel rim of Example 2 and Comparative Example 2 are shown in Table 2. It can be seen that the adoption of the scheme of the present invention has little effect on the conventional mechanical properties of the key parts of the wheel rim, and can ensure the service safety of the wheel.

[0083] Example 3

[0084] A wheel for urban rail vehicles with a narrow hardness range comprises the following components in mass percentage: as shown in Table 1, P 0.010% and S 0.009% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0085] The method for producing urban rail vehicle wheels with a narrow hardness range of Example 3 comprises the following specific steps:

[0086] S1. Put the rolled blank wheel into the furnace and heat it to 855±10℃, and keep it evenly heated for 1.5h to ensure that the whole wheel is evenly heated and fully austenitized.

[0087] S2. Take out the fully austenitized wheel and transfer it to the horizontal quenching table. Use the tread continuous spray quenching method to cool it. Six box-type spray guns are evenly distributed along the circumference of the wheel. The water flow rate of each spray gun is equal. The flow rate L of each spray gun is 20m 3 / h, water outlet speed 6m / s. During the quenching process, the wheel rotates at an angular velocity of 55° / s, the water outlet direction is along the wheel rotation direction, and the water column and the tread tangent form an angle of 30°. The rim thickness B is 70mm, and the quenching time is 240s.

[0088] S3. The surface temperature of the wheel tread after quenching is lower than 100℃. The wheel after quenching is transferred to the tempering furnace through the cooling bed for 5 minutes. Then, the wheel is loaded into the tempering furnace and tempered at a high temperature of 516℃ and kept warm for 3 hours. After tempering, the wheel is taken out and air-cooled. The rim surface is machined with a circular blade of φ20mm in diameter. The total machining amount of the single-side tread is 9mm, the machining line speed is 190m / min, the cutting depth is 0.4mm per cut, the feed rate is 0.9mm per revolution, and the finished tread roughness is Ra 3.2.

[0089] Comparative Example 3

[0090] A wheel comprises the following components in mass percentage: as shown in Table 1, P 0.009% and S 0.009% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0091] The preparation steps and relevant technical parameters of the wheel are the same as those of Example 3. However, the difference from Example 3 is that the tempering average temperature of the wheel in Comparative Example 3 does not exceed 500°C, and here the tempering is performed at an average temperature of 470°C.

[0092] The radial hardness distribution of the nominal rolling circle of the wheels of Example 3 and Comparative Example 3 is as follows: Fig.13 As shown. The radial hardness gradient of the wheel of comparative example 3 is obvious, and the hardness difference between the tread surface and the inside of the rim is 36HB, while the hardness of the tread surface of the wheel of embodiment 3 is significantly reduced, and the gradient is not obvious. The hardness difference between the tread surface and the inside of the rim is only 17HB, and the hardness of the tread sub-surface and the inside of the rim is equivalent to that of the wheel of comparative example 3, achieving the design expectation. The microstructure of the wheel of embodiment 3 at room temperature is pearlite + a small amount of ferrite. The ferrite content at the wear limit (i.e. 35mm from the finished tread) is 3.4±0.3%, the pearlite plate spacing is 144±2nm, and the grain size is 7.5.

[0093] The tensile mechanical properties and Charpy impact energy of the wheel rim of Example 3 and Comparative Example 3 are shown in Table 2. It can be seen that the adoption of the scheme of the present invention has little effect on the conventional mechanical properties of the key parts of the wheel rim, and can ensure the service safety of the wheel.

[0094] The above reference embodiments and drawings provide a detailed description of a urban rail vehicle wheel with a narrow hardness range and a method for preparing the same. This is merely illustrative and not restrictive. Several embodiments may be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for producing urban rail vehicle wheels with a narrow hardness range, characterized in that: The production method comprises the following steps: S1: Take the rolled blank wheel into the furnace for heating and heat preservation; S2: taking out the wheel obtained in step S1 and transferring it to a horizontal quenching table, cooling it by continuous tread quenching, during which the wheel rotates; S3: transporting the wheel obtained in step S2 to a tempering furnace for tempering treatment; In step S2, the tread is cooled by continuous spray quenching, specifically: 6 box-type spray guns are evenly distributed along the circumference of the wheel, and the water flow rate of each spray gun is equal, that is, the flow rate of each spray gun is equal. L 18~20m 3 / h, water outlet speed 6~8m / s; In step S2, the wheel rotates at an angular velocity of 55-65° / s; the water discharge direction of the spray gun follows the wheel rotation direction, and the water column forms an angle of 30-35° with the tread tangent; the spray quenching time t Depending on the wheel rim thickness B Depends, specifically: Rim thickness of blank wheel B For wheels ≤75mm, control the quenching time to 240s≤ t ≤270s; Rim thickness of blank wheel: 75< B For wheels ≤85mm, control the quenching time to 270s< t ≤320s; In step S3, the obtained wheel is taken out and transferred to the tempering furnace through the cooling bed. The transfer time of the cooling bed is 5-8 minutes. The temperature of the entire rim is uniform and stable at 420-470°C. Then the wheel is brought into the tempering furnace with heat. In step S3, the tempering temperature is T 回 510~565℃, and keep warm for 2.5~3h; The urban rail vehicle wheel with a narrow hardness range includes a wheel having the following components in mass percentage: C 0.54-0.63%, Si 0.20-0.50%, Mn 0.70-0.90%, Cr 0.12-0.35%, Mo 0.04-0.10%, Ni 0.05-0.10%, V0.02-0.06%, P ≤0.020%, S ≤0.015%, and the rest being Fe and unavoidable impurities.

2. The production method according to claim 1, characterized in that In step S3, the tempering temperature is T 回 =595-exp[5.81×C+1.14×(Cr+Mo+Ni)+2.11×V]; In the formula, the index value of each element = the content of the element in the steel × 100; T 回 The unit is ℃.

3. The production method according to claim 1, characterized in that In step S1, the wheel is heated to A c3+(60~90)℃, and keep warm for 1~1.5h.

4. The production method according to claim 1, characterized in that The average pearlite plate spacing from the near surface of the wheel rim tread to the inside of the rim obtained in step S2 is 100~170nm.

5. An urban rail vehicle wheel with a narrow hardness range produced by the production method according to any one of claims 1 to 4.

6. The urban rail vehicle wheel with a narrow hardness range according to claim 5, characterized in that: The cross-sectional hardness range of the urban rail vehicle wheel in the narrow hardness range is less than 20HB.

Citation Information

Patent Citations

  • Thermal treatment method of high-carbon steel railway wheels

    CN102021301A

  • High-speed railway wheel capable of effectively improving fatigue limit of wheel disk and manufacturing method thereof

    CN108707818A